The Effectiveness Of Cooperative Learning On Reading Comprehension Skill - Muhimatul Alfiyah (JEET, Journal of English Education and Technology, 2024)
This study aims to know the effect of cooperative learning of typescript strategy on reading comprehension. In the existing knowledge and skill, students viewed as a subject, not an object, and students more important between teach. Despitefully, students, took a hand, attempt, and do with her that the learning, whereas in education refers to current knowledge and skill, the function teacher makes in invention a condition that it may students the developing optimal. This research forms the research of pre-experiment research. The population of this study was the seventh grade of MTs Al Ikhwan Kemudi Duduk Sampeyan Gresik. The method of data collection used is test and observation. The research started by giving pre-test and post-test. The data of the experiment were analyzed by using t-test formula to know the difference of the student’s individual in reading comprehension between cooperative learning in reading comprehension. The result of data analysis and the consideration result of research about the realization cooperative learning of typescript in reading comprehension skill in MTs Al Ikhwan Kemudi Duduk Sampeyan Gresik, be able to procurable that follow: The activity of the teacher, while apply of cooperative learning typescript that has implementable well, the teacher has effective in apply of cooperative typescript. See from the achievement of students in test pre-test and post-test reading comprehension skills; the cooperative learning typescript is very effective use as method learning in MTs Al Ikhwan.